Improving the safety of anticoagulation initiation in patients discharged from the emergency department. (25th October 2022) - Harding, Andrew M; Mitri, Elise; Yeoh, Michael
Abstract: Objective: To improve the safety of anticoagulation initiation by increasing the proportion of patients reviewed by a pharmacist. Methods: An electronic intervention was developed to ensure all patients prescribed anticoagulation on discharge were reviewed by an ED pharmacist. Safe anticoagulation initiation was compared for patients seen and not seen. Results: The intervention increased the number of patients seen by an ED pharmacist. Pre‐intervention ( n = 238) 84.5% of patients were reviewed by a pharmacist. Post‐intervention ( n = 253) 99.6% of patients were reviewed by a pharmacist. Of the 38 patients not reviewed by a pharmacist, 20 (52.6%) had safe anticoagulation initiation and in a sample of 40 patients reviewed by a pharmacist, all 40 (100%) had safe anticoagulation initiation (52.6% vs 100%, P < 0.001). Conclusion: The real‐time electronic intervention improved the number of patients reviewed by a pharmacist. ED pharmacist reviewed patients were more likely to have safe anticoagulation initiation.